2015
DOI: 10.2741/e732
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide and analogues in cancer prevention

Abstract: Andrographis paniculata is a medicinal plant traditionally used for treatment of cough and cold, fever, laryngitis, and several infectious diseases. Extracts of A. paniculata have shown versatile potency against various diseases including cancer. The active biomolecules of A. paniculata mainly are lactone and diterpene. Andrographolide and analogues have been widely used for prevention of different diseases. Andrographolides have shown potent antiinflammatory and anticancer activities. It showed potentials as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 55 publications
(77 reference statements)
2
29
0
Order By: Relevance
“…Recently, natural products or small molecules such as berberine, curcumin, and resveratol have been shown to inhibit cell growth of several human cancers [Lee et al, ; Eo et al, ; Dai et al, ], thus are considered as promising therapeutics against cancers. Andro is such a natural product, which has been shown to possess anti‐cancers activities by the inhibition of cell proliferation, induction of cell cycle arrest, and triggering of apoptosis in several human cancer cells [Preet et al, ; Mishra et al, ; Zhang and Qiu, ; Kishore et al, ]. In the present study, we demonstrated that Andro inhibits chondrosarcoma cell growth by induction of G2/M cell cycle arrest via the fine‐tuning of cell cycle regulators such as p21, p27, and Cyclins (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Recently, natural products or small molecules such as berberine, curcumin, and resveratol have been shown to inhibit cell growth of several human cancers [Lee et al, ; Eo et al, ; Dai et al, ], thus are considered as promising therapeutics against cancers. Andro is such a natural product, which has been shown to possess anti‐cancers activities by the inhibition of cell proliferation, induction of cell cycle arrest, and triggering of apoptosis in several human cancer cells [Preet et al, ; Mishra et al, ; Zhang and Qiu, ; Kishore et al, ]. In the present study, we demonstrated that Andro inhibits chondrosarcoma cell growth by induction of G2/M cell cycle arrest via the fine‐tuning of cell cycle regulators such as p21, p27, and Cyclins (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Andro has previously been reported to exhibit anti‐cancer activities [Mishra et al, ], we then determined whether Andro has an inhibitory effect on cell growth of chondrosarcoma. As shown in Figure A and B, Andro significantly inhibited SW 1353 cell growth in a dose‐ and time‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrographolide (Andro), the active ingredient of the traditional Chinese medicine Andrographis paniculata, has been used primarily for analgesic (12). It has been proved that Andro possess various biological activities such as anti-inflammation, anti-infection, immune system regulation, anti-cardiovascular disease, and anticancer effects (13)(14)(15). Previous studies have shown that Andro exhibited potential antitumor activity in various malignancies, including gastric cancer (16), chondrosarcoma (17) and colorectal cancer (18).…”
Section: Introductionmentioning
confidence: 99%
“…Additional hepatoprotective, antihypertensive, antipyretic, antimalarial, and antithrombotic effects have also been reported, and Andrographis Paniculata has been used in antidotes for snake bites. Moreover, andrographolide (And), extracted and purified from Andrographis Paniculata, is currently prescribed for treatment of inflammation-related diseases, such as laryngitis, upper respiratory tract infection, rheumatoid arthritis, and cancer [11][12][13]. Recent studies have revealed that this herb also has cardiovascular effects [14][15][16], and And has been shown to protect hearts against ischemia/reperfusion [17].…”
Section: Introductionmentioning
confidence: 99%